Human Resources Management in Trouble Time: Strategy to Increase Organization Agility for Digital Transformation in University - Tiwow, Gilly Marlya; Batmetan, Johan Reimon; Sumual, Tinneke E. M.; Sumual, Shelty D.M. (JR Education, 2023)
Digital transformation has become an urgent need for higher education in this contemporary era. In facing emerging challenges and opportunities, human resource management (HR) plays a central role in ensuring the successful adaptation of educational institutions to technological change. This research aims to identify key strategies in HR management that can increase the resilience of higher education organizations during periods of crisis, especially in the context of digital transformation. The research method used is a combination of literature study and empirical research. Through an in-depth analysis of theories and practices related to HR management, as well as case studies of several universities that have successfully adapted to digital transformation, this research identifies various effective strategies. The research results show that effective HR management in the context of digital transformation requires a holistic and adaptive approach. A strategy that includes developing digital skills and competencies, organizational flexibility, increasing employee engagement, and building a culture of innovation is the key to success. In addition, cross-departmental collaboration, transparent communication, and visionary leadership have also proven important in facing digital transformation challenges. This research provides a theoretical and practical basis for universities to design effective HR management strategies to increase organizational resilience in the face of technological change. The practical implications of this research can guide higher education leaders and HR practitioners to face challenges and take advantage of opportunities in the rapidly changing era of digital transformation.